THE ROLE OF RELIGIOUS EXTENDERS IN IMPROVING FAMILY RESILIENCE IN THE RELIGIOUS AFFAIRS OFFICE (KUA) PADANG CITY - Fadil Maiseptian; Erna Dewita; Jasman Jasman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The high rate of divorce, especially in West Sumatra, is an important note for religious extension workers to increase their role and quality in providing counseling. Therefore, fast and progressive action is needed to overcome this. Another phenomenon revealed from the above data is that the divorce case is dominated by the wife's lawsuit. Therefore, it takes the role of religious counselors at the Office of Religious Affairs (KUA) to increase family resilience. The purpose of this study was to determine the role of religious instructors in increasing family resilience in the city of Padang from physical, social, and psychological aspects. Data collection techniques used interviews and were analyzed with the Miles and Huberman models following the stages of data reduction, data display, conclusion. The role of religious counselors in increasing family resilience has been carried out quite well, although not yet maximized because the raw materials are not yet available, the methods used are only advice and lectures and have not been evaluated continuously.